Analysis of enhancement mechanism for thermal conductivity of nanofluids by inelastic X-ray scattering. (July 2021) - Hashimoto, Shunsuke; Yano, Kazuhisa; Hirota, Yasuki; Uchiyama, Hiroshi; Tsutsui, Satoshi
Highlights: The values of high-frequency sound velocity (HFSV) from the nanofluids are higher than that from base ethylene glycol aqueous solution. The solvent molecules around SiO2 nanoparticles are highly restrained in the nanofluids. The HFSV depends on the size of the original SiO2 particles and the HFSV of 300 nm nanofluid is higher than those of any other nanofluids. The correlation can be obtained between HFSV and thermal conductivity for the nanofluids. The collective dynamics of solvent molecules are affected by nanoparticles and subsequently the phonon conduction may be enhanced. Abstract: The inelastic X-ray scattering for the nanofluid composed of silicon dioxide (SiO2 ) nanoparticles (various sizes exceeding 100 nm) and ethylene glycol aqueous solution has revealed one of the mechanisms for the thermal conductivity enhancement of nanofluids, which the addition of a small amount of nanoparticles can improve the thermal conductivity of nanofluids beyond the theoretical value. The high-frequency sound velocity derived from the inelastic X-ray scattering spectra of nanofluids may be generally correlated with the structural relaxation of solvent molecules and corresponding thermal conductivity. It can also clarify the effect of nanoparticles on the thermal transport in nanofluids and the molecular dynamics of the solvent around nanoparticles. The size of the SiO2 particles in the nanofluid, which are 100, 300, 500, and 1000 nm, is approximately 10 times larger than the typical size of nanoparticles considered in research. Nevertheless, the experimental results indicate that SiO2 particles may increase the high-frequency sound velocity in the ethylene glycol aqueous solution because of the highly restricted movement of the solvent molecules around these nanoparticles. The high-frequency sound velocity in the SiO2 nanofluid is proportional to the thermal conductivity and that containing particles 300 nm in size is higher than those of other nanofluids containing particles 100, 500, and 1000 nm in size. Graphical abstract: Image, graphical abstract